Propagação vegetativa de Inga edulis Mart. por estaquia e miniestaquia - Berude, Marciana Christo (2018)
Vegetative propagation techniques, such as cuttings and minicutting, constitute an alternative to overcome difficulties in the sexual propagation. In particular, of species that present peculiar characteristics, like the Inga edulis, of production of recalcitrant seeds. In this way, the objective of this research was to analyze the potential of cuttings and leaf and minicutting as a method of vegetative propagation for Inga edulis and the influence of different concentrations of IBA(indol-3-butyric acid). The vegetative material used in the research was collected from adult plants, present in the arboretum of the experimental area of the Department of Forest and Wood Sciences (DCFM), in the municipality of Jerônimo Monteiro, and juvenile plants of the clonal mini garden formed in the same area. The experiment was carried out in a completely randomized design, with different concentrations of IBA being tested. In the experiment we tested leaf and stem cuttings of adult matrices using seven concentrations of IBA (0, 1000, 2000, 4000, 8000, 16000 and 32000 mg Kg-1 ), five replications for leaf cuttings and four replications for stem cuttings, and in both, each experimental unit was formed by ten stakes. In the experiment of juvenile matrices, it tested leaf and stem minicuttings using five concentrations of IBA (0, 1000, 2000, 4000 and 8000 mg Kg -1 ), with five replicates and each experimental unit containing eight minicuttings. The staking was carried out in 55 cm3 filled with expanded vermiculite. After 45 days in greenhouse the percentage of cuttings and minicuts were analyzed, with callus and rooted. The number of roots, root length, dry shoot mass, root dry mass and total dry mass were also analyzed in leaf and stem minicuttings of juvenile matrices. The roots of the minicuttings were stored and later scanned in a scanner. The images were submitted to the SAFIRA program for surface area quantification and root diameter. The roots of the minicuttings were stored and later scanned in a scanner. The images were submitted to the SAFIRA program for surface area quantification and root diameter. The results indicate that the leaf and stem cuttings of adult matrices presented a low percentage of rooted cuttings, with callus and survival. It was verified that these experiments did not present statistically significant differences for the analyzed variables as a function of the IBA doses. The leaf and shoot minicuttings of juvenile matrices presented 100% survival, and rooting percentages above 70 and 85%, respectively. There was no significant effect for the variables analyzed in the leaf minicuttings treatments. It was observed that the different concentrations of IBA had no significant effect on rooting, callosity, survival, MSPA, MSR, MST and root length. The surface area, diameter and number of roots were significantly influenced by the addition of auxin. It was observed that the addition of 8000 mg Kg-1 AIB in minicuttings favors more vigorous roots and the rooting of minicuttings of Inga edulis can occur without the use of IBA.